Survei Keterampilan Teknik Dasar Atlet Bola Voli - Keswando, Yusril; Sistiasih, Vera Septi; Marsudiyanto, Tulus (Universitas Hamzanwadi, 2022)
Volleyball is a team sport, so players must work together and support each other to become a cohesive team. Thus, to become a compact team or team, all players must have good volleyball skills. The skills of a volleyball player are used to master the basic techniques in volleyball, namely passing, serving, block and smash. The purpose of this research is to find out how good the basic technical skills of volleyball athletes in Sragen Regency are. The method in this study used a survey method while the data collection technique used a test instrument. The results of this study based on the results of descriptive analysis of research data from upper passing, lower passing, upper serving, lower serving and smashes. people (42.42%), “Medium” 12 people (36.36%), “Poor” 0 people (0.00%), “Poorly” 0 people (0.00%). For sons,